Differences in Aspergillus‐specific immune recovery between T‐cell‐replete and T‐cell‐depleted hematopoietic transplants. (16th March 2015) - Perruccio, Katia; Topini, Fabiana; Tosti, Antonella; Gazzola, Maria Vittoria; Messina, Chiara; Martelli, Massimo F.; Caniglia, Maurizio; Velardi, Andrea; Cesaro, Simone
Abstract: Background: After hematopoietic stem cell transplantation, invasive aspergillosis remains one of the most lethal infections. Susceptibility may be due to prophylaxis and treatment of graft‐vs.‐host disease in T‐cell‐replete transplants, and delayed immune rebuilding due to T‐cell depletion in haploidentical transplantation. Methods: We monitored CD4 + T‐cell recovery and anti‐ Aspergillus immune competence in pediatric recipients of T‐cell‐replete matched transplants and of prevalently adult recipients of T‐cell‐depleted matched or haploidentical transplants for hematological malignancies. Results: Although CD4 + T‐cell counts were higher in T‐cell‐replete transplant recipients at all post‐transplant time points, Aspergillus ‐specific T cells were first detected 15–18 months after T‐cell‐replete matched, 7–9 months after T‐cell‐depleted matched, and 9–12 months after haploidentical transplantation, respectively. Incidence of invasive aspergillosis was 22% with 10% mortality after T‐cell‐replete transplants, 0% after T‐cell‐depleted matched, and 7% with 4% mortality after haploidentical transplants. Conclusions: Although T‐cell counts were significantly higher after T‐cell‐replete transplants, post‐transplant immune suppression/GvHD appeared to impair their function. Specific Aspergillus immune competence recovered faster after T‐cell‐depleted transplants, whether matched or haploidentical. T‐cell‐replete transplants were associated with a higher incidence of invasive aspergillosis and Aspergillus ‐related deaths. These results showed that T‐cell depletion without post‐transplant immunosuppression is associated to a faster immune recovery than T‐cell‐replete transplantation.